Postharvest productivity and storage of common double and triple transgenic corn hybrids for green ear consumption (Research, Society and Development, 2022)
The objective was to evaluate the performance of common double and triple transgenic hybrids for the production and post-harvest storage of green corn ears. In the field, the treatments consisted of two corn hybrids (AG 1051 and AG 8677), arranged in a randomized block design, with fourteen replications. For the characteristics evaluated in the laboratory at post-harvest, the treatments consisted of two corn hybrids (AG 1051 and AG 8677) and two types of storage (environment and modified environment), arranged in a completely randomized experimental design, in a 2 factorial scheme. x 2, with five repetitions. The following variables were evaluated: length of the husked and husked ear, diameter of the husked and husked ear, cob diameter, marketable husked and husked ear weight, cob weight, straw, grains, number of rows, average number of grains per ear, number of ears per plant, productivity and weight loss. The triple transgenic hybrid AG 8677 fits within the standards to be marketed 'in natura' as green corn; If the marketing of green corn at the producer level is by weight of the ear 'in natura', AG 1051 is recommended; If marketing is based on the number of ears 'in natura' or by weight of processed grains, AG 8677 is recommended; The environment modified with wet cloths was more effective in reducing weight loss during storage.